2022
DOI: 10.1038/s41598-022-16952-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between two- and three-dimensional methods for offset measurements after total hip arthroplasty

Abstract: The aim of this study was to compare acetabular offset, femoral offset, and global offset measurements obtained after total hip arthroplasty (THA) between a two-dimensional (2D) method and a three-dimensional (3D) method. The subjects were 89 patients with unilateral osteoarthritis who underwent primary THA at our institution. Acetabular, femoral, and global offsets were measured by each of the 2D and 3D methods in native and implanted hips. In native hips, mean acetabular, femoral, and global offsets were 32.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
(39 reference statements)
1
6
0
Order By: Relevance
“…The main limitations of this study include its retrospective design, limited sample size, absence of a control group, high dropout rate, and two-dimensional (2D) radiological evaluation. Our previous study reports the usefulness and accuracy of the three-dimensional (3D) method, in line with previous reports [ 30 , 31 ]. In this study, no CT data was included.…”
Section: Discussionsupporting
confidence: 87%
“…The main limitations of this study include its retrospective design, limited sample size, absence of a control group, high dropout rate, and two-dimensional (2D) radiological evaluation. Our previous study reports the usefulness and accuracy of the three-dimensional (3D) method, in line with previous reports [ 30 , 31 ]. In this study, no CT data was included.…”
Section: Discussionsupporting
confidence: 87%
“…Notably, our study findings were evaluated in the pelvis and femur and were realigned to a unified coordinate system. Similarly, several studies have stated that their parameters were measured using plain radiographs; therefore, FO is not accurately influenced by differences in the rotation of the hip joint [ 5 , 6 , 31 ]. Additionally, hip adduction and abduction also influence LLD and SGL.…”
Section: Discussionmentioning
confidence: 99%
“…Our study is notable in that both the pelvis and the femur were assessed by alignment to a certain coordinate system; to our knowledge, this was the first report using this 3D method. When the studied parameters are assessed using plain radiographs, FO may not be accurate because of the differences in hip rotation 5 . In addition, adduction and abduction of the hip can affect LLD.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, Esbjörnsson et al reported that pain and quality of life were improved, and Bonnin et al reported that the stress of the abductor muscles decreased when the acetabular component was placed slightly medially and the FO was enlarged 3 , 4 . Most of these reported outcomes are based on plain radiographs, which do not show the effects of hip internal and external rotation on FO 5 . In general, the FO is larger in internal rotation and smaller in external rotation; therefore, assessment by plain radiographs is not reproducible.…”
Section: Introductionmentioning
confidence: 99%